Pemrograman Linear Menggunakan Metode Simpleks dalam Optimasi Maksimum pada Proses Produksi Kue Cubit Lumer (Jurnal Manajemen Kreatif dan Inovasi, 2025)
Kue cubit lumer is a traditional snack that is increasingly popular in Indonesia, especially among children and teenagers. This cake has a soft texture with a melting center. This study aims to optimize the production of kue cubit lumer using linear programming method with simplex analysis through Microsoft Excel Solver to determine the optimal production quantity of three variants: original, cheese, and chocolate. The calculation results show that the production of 2 pcs of original cubit cake, 4 pcs of cheese, and 4 pcs of chocolate will generate maximum profit of Rp124,000 per day. The simplex method proved effective in solving production optimization problems by maximizing the use of raw materials and increasing profitability. This study provides guidance for businesses to manage production efficiently to meet market demand and significantly increase profits. This study proves that the simplex method is effective in solving production optimization problems to achieve maximum profit.